ANALISIS WILLINGNESS TO PAY (WTP) MASYARAKAT TERHADAP PENINGKATAN PENGELOLAAN SAMPAH MELALUI TAMAN EDUKASI SAMPAH KELURAHAN PERUMNAS WAYKANDIS, KOTA BANDAR LAMPUNG - Berliani, Miranda; Alam, Firdha Cahya; Setiajaya, Arif (Journal of Science and Applicative Technology; Vol 7 No 2 (2023): Journal of Science and Applicative Technology December ChapterDO - 10.35472/jsat.v7i2.911, 2023)
This study aims to analyze the willingness to pay the people of Perumnas Waykandis Village to improve waste management through a waste education park and analyze the effect of gender, age, education level, profession, and income on people’s willingness to pay. This study uses primary data obtained from surveys by distributing questionnaires to 95 respondents/households. The analytical tools used are the contingent valuation method (CVM) and multiple linear regressions. The contingent valuation method (CVM) aims to determine the WTP value and multiple linear regressions to determine the effect on the community’s willingness to pay to improve waste management through waste education parks. This study indicates that as many as 82 people (86%) of respondents are willing to pay for increased waste management through educational parks, and the remaining 13 (14%) respondents are not. Factors that influence people’s willingness to pay for improving waste management through waste education parks are age, education, and income factors. At the same time, the factors that do not affect people’s willingness to pay are gender and profession.